2016
DOI: 10.18632/oncotarget.10355
|View full text |Cite
|
Sign up to set email alerts
|

Sohlh2 suppresses epithelial to mesenchymal transition in breast cancer via downregulation of IL-8

Abstract: Breast cancer is one of the deadliest cancers worldwide due to its strong metastasis to other organs. Metastasis of breast cancer involves a complex set of events, including epithelial-mesenchymal transition (EMT) that increases invasiveness of the tumor cells. We previously identified sohlh2 is a tumor suppressor in the pathogenesis of ovarian cancer. However, the functions of sohlh2 in breast cancer cell migration and invasion remain unknown. Here we report a novel sohlh2/IL-8 signaling pathway in the invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 39 publications
3
14
0
Order By: Relevance
“…Our previous data showed that sohlh2 could inhibit migration and invasion of breast cancer cells through the suppression of IL‐8 . In this present study, we demonstrated that transcription factor sohlh2 was involved in the regulation of breast cancer growth.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Our previous data showed that sohlh2 could inhibit migration and invasion of breast cancer cells through the suppression of IL‐8 . In this present study, we demonstrated that transcription factor sohlh2 was involved in the regulation of breast cancer growth.…”
Section: Discussionsupporting
confidence: 63%
“…Our previous data showed that sohlh2 could inhibit migration and invasion of breast cancer cells through the suppression of IL-8. 30 In this present study, we demonstrated that transcription factor sohlh2 was involved in the regulation of breast cancer growth. Using both gain- with the observations that support the role of bhlh transcription factor as a negative regulator of cell proliferation in normal, immortalized and cancer cell lines.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…In mouse xenografts, ectopic expression of Shohl2 inhibits metastasis outgrowth, while Shohl2 knockdown boosts metastasis formation. Finally, Shohl2 and IL‐8 protein expressions are negatively correlated in a cohort of 12 breast cancer samples (Ji et al ., ). The CCL18/GM‐CSF/EMT loop described above links EMT to macrophages in a prometastatic pathway.…”
Section: Emt Inflammation and The Metastatic Progressionmentioning
confidence: 97%